2018
DOI: 10.1107/s160057671801350x
|View full text |Cite
|
Sign up to set email alerts
|

Inversion domain boundary structure of laterally overgrown c-GaN domains including the inversion from Ga to N polarity at a mask pattern boundary

Abstract: During epitaxial lateral overgrowth, the lateral polarity inversion of c‐GaN domains from Ga to N polarity, triggered at the boundary of an SiO2 mask pattern, resulted in inversion domain boundaries (IDBs) forming preferentially on the plane, although the formation energy of IDBs on the plane is known to be lower than that on the plane. A model that takes a geometrical factor into consideration can explain this preferential tendency of IDB formation on the plane, and computational simulations based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…circular opening, as illustrated in Figs. 3(c) and 3(d) (Kim et al, 2018). However, once an N-polar GaN seed had been grown over the edge of an SiO 2 mask, the polarity inversion was not observed to occur, even though the lateral growth rate was set to be larger than the vertical growth rate in the previous report (Song et al, 2014), which is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…circular opening, as illustrated in Figs. 3(c) and 3(d) (Kim et al, 2018). However, once an N-polar GaN seed had been grown over the edge of an SiO 2 mask, the polarity inversion was not observed to occur, even though the lateral growth rate was set to be larger than the vertical growth rate in the previous report (Song et al, 2014), which is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 72%
“…To better understand the characteristics of non-edgetriggered polarity inversion, we carefully consider the previous reports of edge-triggered polarity inversion during epitaxial lateral overgrowth. All of the previous reports revealed that the polarity inversion was triggered at the edge of an SiO 2 mask (Song et al, 2014;Wang et al, 2012;Jang et al, 2018;Lee et al, 2018;Kim et al, 2018). In order for the edgetriggered inversion from N polarity to Ga polarity to occur, the lateral growth rate should be larger than the vertical growth rate at the moment when the growth front is at the edge of the SiO 2 mask (Song et al, 2014).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…On this patterned template, N-polar GaN domains were nucleated on the exposed sapphire substrate, and then Ga-polar GaN domains were epitaxially and laterally overgrown on the SiO 2 mask regions by using hydride vapor phase epitaxy. The detailed description to make a controllable polarity-inverted lateral overgrowth of GaN can be found in our previous papers. ,, The identification of the polarity of GaN was carried out by KOH-etching because the surface morphology of KOH-exposed GaN is dramatically polarity-dependent: a Ga-polar surface is very inert, while an N-polar surface is severely etched in such a way that pyramidal hillocks are formed . After N-polar GaN on the opening regions was removed by wet-chemical etching with 85% H 3 PO 4 , the subsequent growth was done in order to recover the fragmented GaN thin film to a continuous one.…”
Section: Methodsmentioning
confidence: 99%
“…Reprinted from [24], Copyright (2016), with permission from Elsevier. domains [36]. After 1 year, the same group reported that polarity switching could also happen in a 'non-edge-triggered' condition [37].…”
Section: Fabrication Of Lps On Sapphire Substratementioning
confidence: 97%